Opportunities and challenges of immuno-oncology: A bibliometric analysis from 2014 to 2023 - Siqi Zhang; Lina Miao; Xiaoxia Tian; Bingxu Yang; Baoping Luo (Human Vaccines & Immunotherapeutics)
The emergence of immuno-oncology (IO) has led to revolutionary changes in the field of cancer treatment. Despite notable advancements in this field, a thorough exploration of its full depth and extent has yet to be performed. This study provides a comprehensive overview of publications pertaining to IO. Publications on IO from 2014 to 2023 were retrieved by searching the Web of Science Core Collection database (WoSCC). VOSviewer software and Citespace software were used for the visualized analysis. A total of 1,874 articles have been published in the IO domain. The number of publications and citations has been increasing annually. This study also examines the primary research directions within the field of IO. In conclusion, this study offers a comprehensive overview of the opportunities and challenges associated with IO, illuminating the current status of research and indicating potential future trajectories in this rapidly progressing field. This study provides a comprehensive survey of the current research status and hot spots within the field of IO. It will assist researchers in comprehending the current research emphasis and development trends in this field and offers guidance for future research directions.